Glutamine and carbohydrate supplements reduce ammonemia increase during endurance field exercise - Carvalho-Peixoto, J.; Cardilo Alves, R.; Cameron, L.-Z. (Applied Physiology, Nutrition, and Metabolism, 2007)
Blood ammonia concentration increases during endurance exercise and has been proposed as a cause for both peripheral and central fatigue. We examined the impact of glutamine and (or) carbohydrate supplementation on ammonemia in high-level runners. Fifteen men in pre-competitive training ran 120 min (~34 km) outdoors on 4 occasions. On the first day, the 15 athletes ran without the use of supplements and blood samples were taken every 30 min. After that, each day for 4 d before the next 3 exercise trials, we supplemented the athletes` normal diets in bolus with carbohydrate (1 g·kg-1·d-1), glutamine (70 mg·kg-1·d-1), or a combination of both in a double-blind study. Blood ammonia level was determined before the run and every 30 min during the run. During the control trial ammonia increased progressively to approximately 70% above rest concentration. Following supplementation, independent of treatment, ammonia was not different (p > 0.05) for the first 60 min, but for the second hour it was lower than in the control (p < 0.05). Supplementation in high-level, endurance athletes reduced the accumulation of blood ammonia during prolonged, strenuous exercise in a field situation.